KAJIAN KUALITAS AIR SUNGAI CILIWUNG - Hasibuan, Ratna Sari (Jurnal Nusa Sylva, 2017)
The Ciliwung Watershed originating from the foot of Mount Pangrango in West Java.Land changes and industrial pollutants and communities living along the Ciliwung River cause the Ciliwung River to be polluted while the Ciliwung River directly or indirectly has an important function for life. The purpose of this study was to determine the water quality of the Ciliwung River based on analysis of pH, temperature, Biological Oxygen Demand, COD (Chemical Oxygen Demand) and plangton identification. The method of taking water samples with the SNI 03-7016-2014 Grab Method was carried out purposively sampling method and analyzed in the UNB Chemical Laboratory. The results of the study were plankton such as phytoplankton Closterium setaceum, Microoimoun strictssium zooplankton, and some shoals such as worms, small crabs, small fish and small shells. The BOD0 value was 13.6418 mg / L, BOD7 which was 12.1855 mg / L and the COD value obtained was 98.00 mg / L. From these results it can be stated that Ciliwung river water was included in class 4 based on PP No. 82 of 2001.Â Â